Laser wakefield acceleration using wire produced double density ramps - M. Burza; A. Gonoskov; K. Svensson; F. Wojda; A. Persson; M. Hansson; G. Genoud; M. Marklund; C.-G. Wahlström; O. Lundh (Physical Review Special Topics. Accelerators and Beams, 2013)
A novel approach to implement and control electron injection into the accelerating phase of a laser wakefield accelerator is presented. It utilizes a wire, which is introduced into the flow of a supersonic gas jet creating shock waves and three regions of differing plasma electron density. If tailored appropriately, the laser plasma interaction takes place in three stages: Laser self-compression, electron injection, and acceleration in the second plasma wave period. Compared to self-injection by wave breaking of a nonlinear plasma wave in a constant density plasma, this scheme increases beam charge by up to 1 order of magnitude in the quasimonoenergetic regime. Electron acceleration in the second plasma wave period reduces electron beam divergence by ≈25%, and the localized injection at the density downramps results in spectra with less than a few percent relative spread.